1998
DOI: 10.1162/089892998563743
|View full text |Cite
|
Sign up to set email alerts
|

Switching Attention without Shifting the Spotlight: Object-Based Attentional Modulation of Brain Potentials

Abstract: Although psychophysical evidence for object-based attention has been reported, corresponding studies with event-related potentials (ERPs) are scarce. Here subjects were presented with perceptual fields containing two superimposed objects (transparent surfaces generated by two sets of dots in rigid rotation around fixation, each set of a different color and direction of motion) or only one object (the same dots but either at rest or all rotating in the same direction). Brief (150-msec) rectilinear displacements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
129
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(146 citation statements)
references
References 79 publications
16
129
1
Order By: Relevance
“…Previous studies which investigated the motion VEP reported an increase in amplitude at electrode sites P3/4 and O1/2 of the international 10±20 system when the moving stimulus was attended and related this augmentation to activity in the dorsal stream Valdes-Sosa et al, 1998). Human fMRI studies showed an increase of metabolic activity related to the processing of moving stimuli in a cortical region which underlies approximately that area measured by P3/4 and O1/2 (Tootell et al, , 1996Sereno et al, 1995).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies which investigated the motion VEP reported an increase in amplitude at electrode sites P3/4 and O1/2 of the international 10±20 system when the moving stimulus was attended and related this augmentation to activity in the dorsal stream Valdes-Sosa et al, 1998). Human fMRI studies showed an increase of metabolic activity related to the processing of moving stimuli in a cortical region which underlies approximately that area measured by P3/4 and O1/2 (Tootell et al, , 1996Sereno et al, 1995).…”
Section: Discussionmentioning
confidence: 92%
“…(3) Is the attentional enhancement of spectral power related to the processing of motion, i.e. resulting from an ampli®cation of neural synchronized activity in the dorsal pathway as suggested by studies using motion evoked VEPs (AnlloVento and Hillyard, 1996;Valdes-Sosa et al, 1998)? A 128-channels EEG montage was used in order to reveal high-density spatial information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention to a spatial location enhances target processing as early as 80 msec after stimulus onset, as shown by a modulation of the P1 event-related potential (ERP) component. Attentional selection of objects or features also takes place early in time, starting around 100-150 msec (Schoenfeld et al, 2007;Valdes-Sosa, Bobes, Rodriguez, & Pinilla, 1998). Attention also modulates other, later stages, as indexed by the P300 or the N400 (Vogel, Woodman, & Luck, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, neither the auditory nor the visual N1 responses are unitary (Naatanen & Picton 1987). In particular, visual N1 peak amplitude and latency are a¡ected by both stimulus and task variables, including response cueing and attention to location or movement (Mangun & Hillyard 1991;O'Donnell et al 1997;Kotchoubey et al 1997;Valdes-Sosa et al 1998). …”
Section: Introductionmentioning
confidence: 99%